Pelatihan Pembuatan Media Pembelajaran Matematika Berbasis Flash Menggunakan Adobe Animate bagi Guru SMP di Kabupaten Kuningan - Uba Umbara; Abdul Rosyid; Dena Latif Setiawan (Jurnal Pengabdian Pada Masyarakat, 2019)
TRAINING FOR MAKING FLASH-BASED MATHEMATICS LEARNING MEDIA USING ANIMATE ADOBE FOR SECONDARY SCHOOL TEACHERS IN KUNINGAN DISTRICT. The purpose of the community partnership program for MGMP teachers at the Kuningan Cluster and Luragung Clusters in Kuningan Regency is to improve teacher competency in creating, developing and implementing flash-based mathematics learning media using Adobe Animate. The problem faced by partners is in implementing mathematics learning in schools that are still dominated through the use of textbooks, so that the teacher’s ability to demonstrate mathematical concepts in learning is still lacking. This was allegedly due to the limited ability of teachers to use learning media, especially ICT-based media. Mathematical MGMP SMP Kuningan cluster and Luragung cluster in Kuningan Regency have a sufficient number of teacher members, but in terms of competence still needs improvement. Understanding of computer-based learning is still very minimal because mathematics teachers have not received specific training on ICT-based mathematics learning. To overcome this condition an activity was packaged in the form of training on the development of flash-based mathematics learning devices using adobe animate for the mathematics MGMP of the Brass Cluster and Luragung Group. This activity was carried out through the following stages: 1) the provision of flash-based mathematics learning and development workshops using adobe animate; 2) mentoring in making flash-based mathematics learning devices using adobe animate; 3) mentoring implementation of flash-based mathematics learning devices using adobe animate; and 4) evaluation and replication.